Faktor-Faktor yang Berpengaruh terhadap Perubahan Laba Bank - Adhista Setyarini (Jurnal Ilmiah Aset, 2009)
This research is performed on order to test influence of the variable Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Biaya Operasional/ Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR), dan Giro Wajib Minimum (GWM) toward Earning Changes. Methodology research as the sample used purposive sampling, sample was accrued 26 Bank Pembangunan Daerah Indonesia. Data analysis with multi linear regression of ordinary least square and hypotheses test used t-statistic and F-statistic at level of significance 5% a classic assumption examination is also being done to test hypotheses. During research period show as variable and data research was normal distributed/ based on test, multicolinearity test, hetersoskedasticity test and autocorrelation test classic assumption deviation has no founded, this indicate that the available data fulfill the condition to use multi linear regression model. This result of research show that variable BOPO and GWM did not influence Earning Changes. Variable CAR, NIM and LDR positive significant influence toward Earning Change. Prediction capability from these variable toward Earning Changes is 20,6% where the balance 79,4% is affected to other which was not to be entered to research model.